Activated sludge behaviour in a batch reactor in the presence of antibiotics: study of extracellular polymeric substances - Avella, A. C.; Essendoubi, M.; Louvet, J. N.; Görner, T.; Sockalingum, G. D.; Pons, M. N.; Manfait, M.; de Donato, Ph (Water science and technology, 2010)
The influence of Erythromycin,Roxithromycin,Amoxicillin, Tetracycline and Sulfamethoxazole on municipal sludge in batch reactors was investigated. The study was focused on extracellular polymeric substances (EPS) as indicator of bacteria sensitivity to toxic agents. The EPS were analysed by UV-Vis and FT-IR spectroscopies and by size exclusion chromatography. It was found that Erythromycin and Roxithromycin induced a significant increase of bound EPS in flocs. This was attributed to a protection mechanism of the bacteria. Erythromycin was the only antibiotic which inhibited COD and nitrogen removal.